(5x+6)-9=24

Simple and best practice solution for (5x+6)-9=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+6)-9=24 equation:


Simplifying
(5x + 6) + -9 = 24

Reorder the terms:
(6 + 5x) + -9 = 24

Remove parenthesis around (6 + 5x)
6 + 5x + -9 = 24

Reorder the terms:
6 + -9 + 5x = 24

Combine like terms: 6 + -9 = -3
-3 + 5x = 24

Solving
-3 + 5x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 5x = 24 + 3

Combine like terms: -3 + 3 = 0
0 + 5x = 24 + 3
5x = 24 + 3

Combine like terms: 24 + 3 = 27
5x = 27

Divide each side by '5'.
x = 5.4

Simplifying
x = 5.4

See similar equations:

| 5(x-10)=45 | | 2x-9=x+1 | | t/12=900/30 | | 4(n+1)=2n-2 | | 1/2x+6=5 | | -60z^5+85z^4+25z^3= | | 6x+4=-16+2x | | 18+x=25 | | 8t-28=5t-7 | | 7.9x=11.85 | | 4/5y=-3/6 | | 23.7=3.5b | | [x-1]=2014 | | 40/x=5 | | 9-2x=x+1 | | -1/3x=-1/6 | | 12+5m=8m | | (12x-6y)(1/2x+3/2y) | | 14+x=23 | | x-10=6x-60 | | 3x=36-(6x+54) | | 3x=6-(6x+54) | | -7x+1=-34 | | -3x-1=-x+5 | | 104/20= | | 10=6a+-9a+a | | 1/3*21/2 | | d^2-33d-180=0 | | 4m+2-20m+48= | | 4x-12=2(x+4) | | X^2+7x+35=-5x | | (x-3/5)=(2/3) |

Equations solver categories